(untitled) (International Journal of Physiotherapy, 2019)
Background: In recent years, many tests have been developed to evaluate the mobility and functional capacity of people with neurological disorders (Hemiplegia, MS). The purpose of this study was to test the reliability and additionally to determine the measurement error of TMT and TUG in adults with neurological disorders (hemiplegia, MS). Methods: In the study of tests 20 adults (11 with multiple sclerosis and 9 with hemiplegia) who were retrospectively registered participated. The average age of adults was 38.7 ± 13.9 years old and their average body mass was 65.1 ± 13.1kg. The Greek version of the tests and a Nikon 5300 digital camera for video recording were used for data collection. ICC was calculated by means of a two-way ANOVA model. Results: The results showed that there were no statistically significant differences between the two independent evaluators and that the TMT (ICC > 0,936 ) and TUG (ICC> 0,996) had strong reliability. Conclusions: Overall, the results of the present investigation provided considerable evidence suggesting that the tests TMT and TUG are reliable and can be used to evaluate kinetic and balance disorders. Therefore, it was concluded that the tests should be applied to reliably estimate the mobility and functional ability of adults with neurological disorders.